Social responsibility in purchase and consumption: A study of the Portuguese consumer behavior - Filipe, S.; Marques, S.; Salgueiro, M.F. (Proceedings ICIEMC 2015, 2015)
In the last decades, academic literature has been putting a notorious emphasis on the concepts of socially responsible consumer. However, literature also shows the existence of differences in the behavioural attitudes of consumers, due to the influence of the socio-cultural context and of social interactions. In the case of Portugal, there is no thorough study that analyzes the propensity of individuals for socially responsible consumption. Thus, this paper aims to examine the determinants of Socially Responsible Purchase and Disposal (SRPD), building on the work of Weeb, Mohr and Harris (2008), by analyzing the socio-demographic consumer profile. Exploratory interviews were used and collected data were subject to qualitative analysis. Additionally, a convenience sample of 1027 Portuguese adults answered to an online questionnaire. The results show that the socially conscious behaviour appears to be well established among the consumers. Also, individuals with certain demographic characteristics differ in their levels of social consciousness in purchase and consumption.